Mutagenic effects of pesticides on Enteric Bacteria and their role in the rise of antimicrobial resistance (AMR) - Gupta, Somnath (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.